Molecular Mechanisms of Dicentra Formosa's Analgesic Effect - Royale Gray-Lee; Jesun Lee (Elsevier, 2020)
Background: Surgeons, Native Americans, and Eclectics have all sworn to the multiple healing properties including anthelmintic, analgesic, and anti-cancer effects that Dicentra Formosa possesses. However, none of the above provided any scientifically proven data to conclude the healing properties of Dicentra Formosa as fact. Purpose: Here, I have examined the analgesic effect of Dicentra Formosa in two pain models and also identified the molecular target for the analgesic effect of Dicentra. Experimental approach: In the chronic pain model of carrageenan-induced inflammation and sciatic nerve ligation, I observed that the threshold for thermal and mechanical nociception was increased in Dicentra-treated mice compared to the vehicle-treated group. As TRP channels, especially TRPV1 and TRPA1 are known to play a crucial role in the hypersensitivity to thermal and mechanical stimuli, we proceeded to test the analgesic effect of Dicentra Formosa on TRPV1, TRPA1 channel activities; followed by calcium imaging and patch clamp recordings. Key Results: Calcium imaging and patch clamp recordings revealed Dicentra Formosa to have an antagonistic effect on the TRPA1 channel comparable to the known TRPA1 antagonist, HC-030031. However, Dicentra Formosa showed no inhibitory effect on the TRPV1 channel. Conclusions and Implications: Therefore, Dicentra Formosa shows a substantial analgesic effect in inflamed and neuropathic pain, which is presumably mediated by the inhibition of TRPA1 channel. These findings are the first scientific report for analgesic effect of Dicentra Formosa, which provides potential therapeutic promise of Dicentra Formosa for pain relief.